6 - Extension Needs of Women Cassava Farmers in Igueben and Esan Northeast Local Government Areas of Edo State, Nigeria: 10.4314/ad.v27i1.22153 - Onemolease, Eddy (Africa Development, 2022)
Women's advancement is predicated upon their educational development. But what exactly should this education focus on vis-à-vis cassava production? Answers to this question pre-suppose an understanding of their knowledge of modern cassava production-related practices. The study addresses these issues by gathering data from 120 women cassava farmers in two selected local government areas of Edo State. Results show that the respondents were relatively young, largely illiterate and had long years of farming experience. Their levels of knowledge of improved cassava varieties and fertilizers were high while they were low for herbicides and recommended agronomical practices. There is therefore a need for the agricultural extension agency to focus its educational efforts on these problems, in addition to providing such farmers with information on sources of farm chemicals, credit and market opportunities.